Influence of the Reynolds number on the thermal effectiveness of tubular heat exchanger subjected to electromagnetic field-based antifouling treatment in an open once-through seawater cooling system. (25th July 2018) - García, Sergio; Trueba, Alfredo
Graphical abstract: Highlights: Biofouling adhesion under turbulence flow was investigated. Effectiveness-NTU during antifouling treatment is improved. Increasing the Re can improve the AF EMF treatment on a seawater cooling system. Re on biofilm characteristics is shown as important variable. Abstract: Biofouling adhesion on heat exchanger surfaces reduces the thermal effectiveness of the heat transfer process. The main purpose of this work was to investigate the influence of the turbulent flow regime on an electromagnetic field (EMF)-based antifouling (AF) treatment in a tubular heat exchanger cooling seawater system and to determine the resulting effectiveness-number of transfer units (ε-NTU). Experiments were performed for turbulent flow corresponding to Reynolds numbers ( Re ) of 9504, 14, 257, 19, 009 and 28, 514, which are normal operating conditions for tubular heat exchangers in which biofouling usually occurs. The best ε-NTU value was improved by 14% for the Re of 28, 514 compared with the best value for untreated water. Furthermore, the Re assayed were associated with improved heat transfer resistance. The best AF rate was as high as 20% for a Re of 28, 514. Additionally, the biofouling film for the case of seawater treated at 28, 514 Re flow was thinner, with a lower concentration of solids, which improved the thermal effectiveness. The EMF-based AF treatment has great potential for improving thermal effectiveness and mitigating biofouling in tubular heat exchangers.